Mass Fabrication of 3D Silicon Nano‐/Microstructures by Fab‐Free Process Using Tip‐Based Lithography. Issue 4 (28th December 2020) - Jo, Jeong‐Sik; Choi, Jihoon; Lee, Seung‐Hoon; Song, Changhoon; Noh, Heeso; Jang, Jae‐Won
Abstract: Methods for the mass fabrication of 3D silicon (Si) microstructures with a 100 nm resolution are developed using scanning probe lithography (SPL) combined with metal‐assisted chemical etching (MACE). Protruding Si structures, including Si nanowires of over 10 µ m in length and atypical shaped Si nano‐ and micropillars, are obtained via the MACE of a patterned gold film (negative tone) on Si substrates by dip‐pen nanolithography (DPN) with polymer or by nanoshaving alkanethiol self‐assembled monolayers (SAMs). Furthermore, recessed Si structures with arbitrary patterning and channels less than 160 nm wide and hundreds of nanometers in depth are obtained via the MACE of a patterned gold film (positive tone) on Si substrates by alkanethiol DPN. As an example of applications using protruded Si structures, nanoimprinting in an area of up to a centimeter is demonstrated through 1D and 2D SPL combined with MACE. Similarly, submicrometer polydimethylsiloxane (PDMS) stamps are employed over millimeter‐scale areas for applications using recessed Si structures. In particular, the mass production of arbitrarily shaped Si microparticles at submicrometer resolution is developed using silicon‐on‐insulator substrates, as demonstrated using optical microresonators, surface‐enhanced Raman scattering templates, and smart microparticles for fluorescence signal coding. Abstract : Mass fabrication of 3D silicon nano‐/microstructures and atypical shaped silicon microparticles is developed through scanning probe lithography in conjunction with metal‐assisted chemical etching. Fabricated structures are successfully utilized as nanoimprinting stamps, polydimethylsiloxane templates, optical resonators, surface‐enhanced Raman scattering templates, and fluorescence signal‐coded smart particles.